2015
DOI: 10.1016/j.scitotenv.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Indoor particulate matter in four Belgian heritage sites: Case studies on the deposition of dark-colored and hygroscopic particles

Abstract: Atmospheric total suspended particulate (TSP) was passively sampled by means of deployed horizontal and vertical filters in various rooms of four Belgian cultural heritage buildings, installed with various heating/ventilation systems. Soiling/blackening and deposition of inorganic, water-soluble aerosol components were considered. The extent of soiling was determined by means of two independent methods: (1) in terms of the covering rate of the samplers by optical reflection microscopy and (2) the reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Nonetheless, it needs to be mentioned that the presence of K + in the corrosion products of a copper alloy is not sufficient, on its own, to confirm a chemical interaction with glass. This cation, in fact, often occurs in airborne particulate matter ( 20 , 21 ) and might therefore be present on the metal because of deposition and soiling ( 22 ). Similarly, Cu and Zn might be also present in the bulk composition of the glass, particularly linked to coloring agents ( 23 , 24 ), and therefore might not be associated to a chemical interaction with brass.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, it needs to be mentioned that the presence of K + in the corrosion products of a copper alloy is not sufficient, on its own, to confirm a chemical interaction with glass. This cation, in fact, often occurs in airborne particulate matter ( 20 , 21 ) and might therefore be present on the metal because of deposition and soiling ( 22 ). Similarly, Cu and Zn might be also present in the bulk composition of the glass, particularly linked to coloring agents ( 23 , 24 ), and therefore might not be associated to a chemical interaction with brass.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting correlations were weak with the exception of sodium relative to magnesium (R 2 = 0.91 indoor and 0.94 outdoor) and sodium relative to chloride and magnesium indoor (R 2 > 0.86). Indeed, salts such as NaCl and MgCl 2 (Anaf et al, 2014) could be present indoors, denoting an impact of sea salt (transport for our case) or building materials, respectively (mortars according to Krupińska et al, 2013).…”
Section: Pollutant Statisticsmentioning
confidence: 99%
“…There is much information in the scientific literature about indoor particles and dust, their characteristics and their impact on cultural heritage (e.g., Anaf, et al, 2015;Grau-Bove and Strlič, 2013;Daher, et al, 2011;de Bock, et al, 1996), the cleaning, treatment and conservation of soiled paintings, and mitigation and management strategies (e.g., Wilson and van Snick, 2017;Ormsby and Learner, 2016;Mecklenburg, Charola and Koestler, 2010;Lithgow, et al, 2005), including economic considerations related to housekeeping (Lloyd, Brimblecombe and Lithgow, 2007). But little information, and to our knowledge few case studies, is available about the relationship between the historical air quality, observed soiling, preventive mitigation actions and future predicted conservation costs for canvas paintings, which is the topic of this study.…”
Section: Research Articlementioning
confidence: 99%